Microwave-assisted in situ large scale synthesis of a carbon dots@g-C3N4 composite phosphor for white light-emitting devices. (8th January 2020) - Meng, Li; Ushakova, Elena V.; Zhou, Zhengjie; Liu, Enshan; Li, Di; Zhou, Ding; Tan, Zhanao; Qu, Songnan; Rogach, Andrey L.
Abstract : A composite phosphor comprising carbon dots and g-C3 N4 is prepared on a large scale through a green microwave assisted in situ heating method, and is used for fabrication of white LEDs with a power efficiency of up to 42 lm W −1 . Abstract : Sustainable, environment-friendly phosphors produced from cheap and readily available precursor materials using green preparation processes are in high demand for lighting applications. Herein, a composite phosphor comprising carbon dots (CDs) and graphitic carbon nitride (g-C3 N4 ) is prepared on a large scale from citric acid and urea in water, through a green microwave assisted in situ heating method. An optimized CDs@g-C3 N4 composite with a 1 wt% loading of CDs shows a strong green emission under 410 nm excitation, with a photoluminescence quantum yield of 62% in the solid state. Using this composite as a phosphor in the color conversion layer, a white light emitting diode with a power efficiency of up to 42 lm W −1 is fabricated.